Performance Evaluation of Real-time DustTrak Monitors for Outdoor Particulate Mass Measurements in a Desert Environment - Wasim Javed; Bing Guo (Aerosol and Air Quality Research)
Abstract Using the filter-based gravimetric technique as the reference method, this study aimed to evaluate the performance of the TSI DustTrak DRX® aerosol monitor, which offers real-time measurements, and establish suitable factors for bias correction in real-world operating conditions. Overall, the DustTrak demonstrated high precision in tracking the PM2.5 and PM10 mass concentrations; however, the measurements significantly deviated from those obtained via the reference method, showing an overestimation by a factor of ~2 for the fine fraction and an underestimation by ~20% for the coarse one. Applying a correction factor based on a constant proportion produced an acceptable level of accuracy, but utilizing one adjusted for humidity achieved even better results. These factors can also be used to enhance the accuracy of DustTrak measurements under comparable conditions, i.e., for aerosol with similar properties in similar environments. Additionally, the proposed approaches can serve as a model for field calibration and measurement data correction in other studies employing various types of real-time optical monitors.